Derivaciones urinarias del tracto urinario inferior en el anciano. - Esteban Fuertes, M.; Luengo Alpuente, S.; Mohamed Mohamed-abdallah, Z.; Moreno Sierra, Jesús; Ramírez Fernández, J.C.; Rapariz, M.; Resel, Luis; Salinas Casado, J.; Silmi Moyano, A.; Begara Morillas, F. (Clínicas Urológicas de la Complutense, 1993)
Sin resumen